Migrants and their families in the home country: a bi-directional influence on voting behaviour. Issue 3 (2nd July 2020) - Grad, Marius; Gherghina, Sergiu; Ivan, Adrian
ABSTRACT: The voting behaviour of migrants has been studied extensively but limited attention has been paid to how the discussion with families in the home country can be important. This article analyzes under what circumstances migrants influence or are influenced by their families in voting decisions. The analysis uses individual-level data from a survey conducted in 2018 on a sample of 1, 839 Romanian migrants. The results indicate that most migrants are not engaged in acts of persuasion about voting. Those who influence their families have a direct interest in the election results, are informed about what happens in the country and are politically active. The migrants who are influenced by their families have limited experience in the countries of residence and strong ties to their home country.